Antioxidant and antibacterial potential of bioactive extraction from Cadaba glandulosa leaves - Sivakumar S. Moni; Fahad Y. Sabei; Ahmad Salawi; Maksood Ali; Ibrahim Mohammed Hadi; Jobran M. Moshi; Zia Ur Rehman; Mohamed Eltaib Elmobark; Sarfaraz Ahmad; Ogail Yousif Dawod; Hanan M. Alsabei (PLoS ONE, 2026)
This study investigated the bioactive components and explored the antioxidant and antibacterial properties of the methanolic leaf extracts of Cadaba glandulosa (MLCG). The observed activity is related to the diverse chemical composition of the extract as determined by gas chromatography-mass spectrometry (GC-MS) analysis, which tentatively identified 18 distinct compounds. Notable compounds include methyl dodecanoate, methyl tetradecanoate, 9,12-octadecadienoyl chloride, hexadecanoic acid methyl ester, palmitoleic acid, anethole, brefeldin A and oleic acid. The antioxidant tests showed a significant scavenging activity of 88.2% at a concentration of 381.5 µg/mL, which underlines the effectiveness of the extract in neutralizing free radicals. The total phenolic content in MLCG was found to be 79.5%, corresponding to 250.8 mg of gallic acid equivalents (GAE)/ mL.The antibacterial activity of MLCG showed variability between bacterial strains, with the strongest inhibition observed against Staphylococcus aureus and Streptococcus pyogenes , both Gram-positive bacteria. The extract showed moderate activity against Gram-negative bacteria such as Escherichia coli and Pseudomonas aeruginosa , while the least activity was observed against Klebsiella pneumoniae . In this study, the impressive antioxidant and antibacterial properties of MLCG underline the therapeutic potential of Cadaba glandulosa as a natural source of antioxidant and antibacterial agents.